Change in the ophthalmoscopical optic disc size and shape in a 10-year follow-up: the Beijing Eye Study 2001–2011 - Jonas, Jost B; Zhang, Qi; Xu, Liang; Wei, Wen Bin; Jonas, Rahul A; Wang, Ya Xing (British journal of ophthalmology, 2023)
BackgroundTo assess prevalence and associated factors of changes in the ophthalmoscopic optic disc size and shape.MethodsThe case–control study included all highly myopic eyes (myopic refractive error ≤−6.0 diopters) and a randomly selected group of non-highly myopic eyes, examined in the population-based Beijing Eye Study 2001 and 2011.ResultsThe study included 89 highly myopic eyes (age:65.0±9.8 years) and 86 non-highly myopic eyes. Reduction in ophthalmoscopic disc size (prevalence, high myopia: 30 (33.7%) eyes; non-high myopia: 7 (8.1%) eyes) was associated with non-circular gamma zone enlargement (OR: 19.4; 95% CI: 6.7 to 56.6; p<0.001) and disc-fovea line elongation (OR: 2.80;95% CI: 1.12 to 6.98; p=0.03). Disc size reduction was correlated with a disc diameter shortening in direction of the widest gamma zone enlargement (correlation coefficient r=34; p=0.01). The perpendicular disc diameter remained mostly unchanged, resulting in an ovalisation of the ophthalmoscopic disc shape. Enlargement of the ophthalmoscopic disc size (prevalence, high myopia: 22 (24.7%) eyes; non-high myopia: 4 (4.7%) eyes) was associated with circular gamma zone enlargement (4.99; 95% CI: 1.95 to 12.8; p=0.001) and high myopia (OR: 4.29; 95% CI: 1.34 to 13.8; p=0.01).ConclusionsMyopic axial elongation may lead first to a Bruch’s membrane (BM) opening (BMO) shift into the foveal direction leading to BM overhanging into the nasal intrapapillary compartment, development and enlargement of gamma zone at the temporal disc side, reduction in the ophthalmoscopically visible disc area and ovalisation of the ophthalmoscopic disc shape. In a second step, an axial elongation-associated BMO enlargement may lead to a circular gamma zone increase and, due to the retraction of BM at the nasal disc border, to an enlargement of the ophthalmoscopically visible optic disc.